Greenwashing: o problema do ESG nas empresas transnacionais em face da legislação brasileira - Nalini, Ana Rita de Moraes (2024)
The term “greenwashing” refers to the practice of companies presenting a misleading or exaggerated image of environmental responsibility. In the current scenario, many transnational companies are adopting ESG (Environmental, Social, and Governance) policies to demonstrate their commitment to environmental, social, and governance issues. However, the lack of genuineness or the manipulation of these practices to appear environmentally friendly, without concrete actions to support such claims, raises significant concerns, especially within the Brazilian context. This problem is particularly relevant in the context of transnational companies, where the alleged adherence to sustainability often does not correspond to real actions. In Brazil, environmental protection and the principles applied in the economic order are clearly established in the constitutional plan. The Brazilian Federal Constitution of 1988 provides a robust legal framework for environmental protection. Article 225 establishes that "everyone has the right to an ecologically balanced environment, a common good for the people and essential to a healthy quality of life", imposing on the government and the community the duty to defend and preserve it for present and future generations. Furthermore, Article 170, Section VI, provides that the economic order must observe the principle of environmental protection, indicating that economic activity must reconcile development and environmental preservation. It follows that the development of economic activity in the country, when promoted by transnational companies, is primarily bound by the provisions of the constitutional text. Respect for social values, environmental protection, human dignity, national sovereignty and the valorization of labor are unquestionable.